Penetrance of Parkinson's Disease in LRRK2 p.G2019S Carriers Is Modified by a Polygenic Risk Score. Issue 5 (20th January 2020) - Iwaki, Hirotaka; Blauwendraat, Cornelis; Makarious, Mary B.; Bandrés‐Ciga, Sara; Leonard, Hampton L.; Gibbs, J. Raphael; Hernandez, Dena G.; Scholz, Sonja W.; Faghri, Faraz; ,; Nalls, Mike A.; Singleton, Andrew B.
Abstract: Background: Although the leucine‐rich repeat kinase 2 p.G2019S mutation has been demonstrated to be a strong risk factor for PD, factors that contribute to penetrance among carriers, other than aging, have not been well identified. Objectives: To evaluate whether a cumulative genetic risk identified in the recent genome‐wide study is associated with penetrance of PD among p.G2019S mutation carriers. Methods: We included p.G2019S heterozygote carriers with European ancestry in three genetic cohorts in which the mutation carriers with and without PD were selectively recruited. We also included the carriers from two data sets: one from a case‐control setting without selection of mutation carriers and the other from a population sampling. Associations between polygenic risk score constructed from 89 variants reported recently and PD were tested and meta‐analyzed. We also explored the interaction of age and PRS. Results: After excluding eight homozygotes, 833 p.G2019S heterozygote carriers (439 PD and 394 unaffected) were analyzed. Polygenic risk score was associated with a higher penetrance of PD (odds ratio: 1.34; 95% confidence interval: [1.09, 1.64] per +1 standard deviation; P = 0.005). In addition, associations with polygenic risk score and penetrance were stronger in the younger participants (main effect: odds ratio 1.28 [1.04, 1.58] per +1 standard deviation; P = 0.022; interaction effect: odds ratio 0.78 [0.64, 0.94] per +1 standard deviation and + 10 years of age; P = 0.008). Conclusions: Our results suggest that there is a genetic contribution for penetrance of PD among p.G2019S carriers. These results have important etiological consequences and potential impact on the selection of subjects for clinical trials. © 2020 International Parkinson and Movement Disorder Society